2016
DOI: 10.18632/oncotarget.12931
|View full text |Cite
|
Sign up to set email alerts
|

G6PC3, ALDOA and CS induction accompanies mir-122 down-regulation in the mechanical asphyxia and can serve as hypoxia biomarkers

Abstract: Hypoxia influences different cellular biological processes. To reveal the dynamics of hypoxia's effects on miRNA regulation in vivo, we examined the expression levels of all miRNAs in human brain and heart specimens from cases of mechanical asphyxia compared with those from cases of craniocerebral injury and hemorrhagic shock. We further validated differently expressed miRNAs in another 84 human specimens and rat models. We found that mir-122 was significantly down-regulated and that its putative targets G6PC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 31 publications
1
20
0
1
Order By: Relevance
“…In addition, we found a strong and direct correlation between liver injury and miR−122-5p (r = 0.91, p < 0.0001), which confirms previous observations by others (49,50), and which can be explained not only by passive release but also by the augmentation of miR-122 in the liver. MiR-122 was also found to play a role in the hypoxia responses that regulate glucose and energy metabolism (51). In addition, it was recently reported that ER stress impacts on miR-122 promoter activity (52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found a strong and direct correlation between liver injury and miR−122-5p (r = 0.91, p < 0.0001), which confirms previous observations by others (49,50), and which can be explained not only by passive release but also by the augmentation of miR-122 in the liver. MiR-122 was also found to play a role in the hypoxia responses that regulate glucose and energy metabolism (51). In addition, it was recently reported that ER stress impacts on miR-122 promoter activity (52).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-101 expression protects cardiac fibroblasts from hypoxia-induced apoptosis [43]. In a rat hypoxia model, miR-122 and its target genes play roles in the hypoxia responses that regulate glucose and energy metabolism and serve as potential biomarkers of mechanical asphyxia [44]. All these results support the concept that miRNAs regulate the response to hypoxia.…”
Section: Discussionmentioning
confidence: 89%
“…As a catalytic enzyme, ALDOA represents one of the key enzymes in the glycolysis process. Of note, it plays a role in the hypoxia responses regulating both glucose and energy metabolism and can serve as hypoxia biomarkers [41]. Ischemic stroke represents a typical atherosclerosis-related disease.…”
Section: Discussionmentioning
confidence: 99%